The impact of digital fabrication in contemporary Portuguese architecture - Susana, Neves (2017)
The use of digital fabrication tools in Portuguese architecture is a very recent approach and it is still making its first steps. With an experimental character at the beginning, allied with the industry or with the academic environment, today the use of digital fabrication starts to gain impact in Portuguese architecture and is beginning to answer the growing market demand for “mass customization” (Mitchell, 2001). This research focuses on understanding the current context and connection of digital fabrication in Portuguese architecture until today, based on the professional path of four Portuguese architects using digital fabrication in different approaches.